The British General Election of 2024 - Ford, Robert. author. aut Link
XL, 775 p. 152 illus., 96 illus. in color.
Keywords: ‘‘Comprehensive, detailed, nuanced, thoughtful. This is a brilliant account of what went on, with the space and patience for the details and subtleties that would otherwise all too easily be lost.” —Chris Mason, Political Editor BBC News "This book is my idea of perfection, tying together the very best data and psephology to get under the skin of the nation alongside a brilliant, narrative read that takes you deep inside the campaigns.” —Anushka Asthana, US Editor, Channel 4 News and author of Taken As Red: How Labour Won Big and the Tories Crashed The Party "A masterpiece: both in terms of understanding how voters moved, how governments changed, and the thinking of the opposition, the best single volume you are likely to read on the election of 2024" —Stephen Bush, Financial Times “We’re living through a remarkable period in political history and there is no better way to understand it, than to read this masterpiece of analysis and story-telling.” —Evan Davis, BBC Radio 4 PM “A vital guide to the 2024 election and a frank account of the political chaos in the dying days of the last Tory administration, this remarkable book serves as a reminder of egos, in-fighting and ebbing power.” —Kitty Donaldson, Chief Political Commentator, The i The British General Election of 2024 is the definitive account of a landmark election, featuring an unprecedented Conservative collapse, a Labour Commons landslide, and record fragmentation in voters' choices. Built on unparalleled access to all the key players, this account weaves together a compelling insider account of how the campaign was fought with rigorous analysis of how, when and where this sea change election was won and lost. The 22nd volume in a prestigious series dating back to 1945, this offers something for everyone, from Westminster insiders and politics students to the interested general reader, who wants to understand one of the most dramatic swings of the electoral pendulum in living memory. Robert Ford is Professor of Political Science at Manchester University, UK. Tim Bale is Professor of Politics at Queen Mary University of London, UK. Will Jennings is Professor of Political Science and Public Policy at the University of Southampton, UK. Paula Surridge is Professor of Political Sociology at the University of Bristol, UK.